Existence and Nonexistence of Entire Large Solutions for Some Semilinear Elliptic Equations (Journal of Partial Differential Equations, 2008)
In this note, we consider positive entire large solutions for semilinear elliptic equations Δu = ρ(x)f(u) in R^N with N ≥ 3. More precisely, we are interested in the link between the existence of entire large solution with the behavior of solution for -Δu = ρ(x) in R^N. Especially for the radial case, we try to give a survey of all possible situations under Keller-Osserman type conditions.